2011
DOI: 10.3324/haematol.2011.050799
|View full text |Cite
|
Sign up to set email alerts
|

Newly diagnosed immune thrombocytopenia in children and adults: a comparative prospective observational registry of the Intercontinental Cooperative Immune Thrombocytopenia Study Group

Abstract: BackgroundPrimary immune thrombocytopenia is a bleeding diathesis with an unknown etiology in predisposed individuals with immune disturbances. Although it is claimed that children and adults differ in clinical and laboratory aspects, few data exist to corroborate this observation. Our objective was to assess comparative data from children and adults with newly diagnosed immune thrombocytopenia. Design and MethodsClinical and laboratory data of 1,784 children and 340 adults were extracted from the Pediatric an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
109
1
12

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(136 citation statements)
references
References 16 publications
(18 reference statements)
9
109
1
12
Order By: Relevance
“…Results are descriptive, including 95% exact confidence intervals. A one-sample proportion test compare the frequency of occult hemorrhage by site (urine, stool, CNS) with the incidence of overt hemorrhage in children with ITP reported in the literature [17][18][19][20] (Table I). The incidence of blood in the urine and stool reported in the literature for healthy children [21][22][23] was used as a comparison group.…”
Section: Introductionmentioning
confidence: 99%
“…Results are descriptive, including 95% exact confidence intervals. A one-sample proportion test compare the frequency of occult hemorrhage by site (urine, stool, CNS) with the incidence of overt hemorrhage in children with ITP reported in the literature [17][18][19][20] (Table I). The incidence of blood in the urine and stool reported in the literature for healthy children [21][22][23] was used as a comparison group.…”
Section: Introductionmentioning
confidence: 99%
“…While some studies characterize pediatric ITP as benign, describing major bleeding as rare [15][16][17][18], other studies have found major bleeding to be more common [19], with rates comparable with those seen in adults [20]. One analysis of 40 cases of ICH in children with ITP found a mortality rate of 25% with ICH and a reported incidence of ICH ranging from 0.19% to 0.78% [21]; other reports have also had varying incidence rates of ICH in pediatric ITP [11,13,20].…”
Section: Introductionmentioning
confidence: 99%
“…One analysis of 40 cases of ICH in children with ITP found a mortality rate of 25% with ICH and a reported incidence of ICH ranging from 0.19% to 0.78% [21]; other reports have also had varying incidence rates of ICH in pediatric ITP [11,13,20]. Regarding infection/sepsis, there are isolated reports of sepsis both with and without splenectomy [19,22]; the latter may coexist with unrecognized immunodeficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, while patients may be severely thrombocytopenic, they rarely present with severe bleeding. Therefore, ITP is usually recognised as a benign condition, with at least 75% of children having minor or no bleeding in spite of extremely low platelet counts (10,11). Nevertheless, severe haemorrhages, such as intractable epistaxis, gastrointestinal bleed or intracranial haemorrhages (ICH), may occur (12).…”
Section: Introductionmentioning
confidence: 99%